2017
DOI: 10.1017/s1368980017001033
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perception of child overweight status and its association with weight-related parenting practices, their children’s health behaviours and weight change in China

Abstract: In China, mothers who perceive their child as overweight are more likely to encourage their child to exercise and modify their diet for weight management, but this encouragement does not seem to improve the child's health behaviours and weight status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
(46 reference statements)
0
32
0
Order By: Relevance
“…In China, children’s self‐perceived weight status has been shown to be substantially influenced by their mothers’ perceptions of the child’s weight status. In one study, mothers and children had 77.1% agreement in their perception of the child’s weight status, and about 10% of children and their mothers underestimated the weight status of the child . In particular, several studies have found that Chinese boys are more likely to underestimate their weight status than girls .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, children’s self‐perceived weight status has been shown to be substantially influenced by their mothers’ perceptions of the child’s weight status. In one study, mothers and children had 77.1% agreement in their perception of the child’s weight status, and about 10% of children and their mothers underestimated the weight status of the child . In particular, several studies have found that Chinese boys are more likely to underestimate their weight status than girls .…”
Section: Discussionmentioning
confidence: 99%
“…Children desiring thinner bodies were more likely to attempt dieting to change their weight and were less likely to feel that they had enough physical activity compared with those who had consistent self‐assessed body image versus desired body image . Other longitudinal studies have revealed that being labeled as fat or having a negative self‐perceived body image is associated with higher weight gain (e.g., β in BMI = 0.38 [SE = 0.13], P < 0.01 and 0.25 [95% CI: 0.10‐0.39] and an increased risk of obesity (e.g., odds ratio of having obesity = 1.6 [95% CI: 1.20‐2.30] than their counterparts . Increased screen time, less breakfast consumption , and depression symptoms among children perceiving themselves as fat have suggested that children’s body dissatisfaction is accompanied by greater psychosocial distress and low self‐esteem regardless of gender, age, weight status, ethnicity, or socioeconomic status , which has evolved from internalized stigmatization of obesity by family, peers, and social media .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that parents who are overweight themselves are more likely to correctly identify their overweight/obese child as such (Peyer et al, 2015), while others indicate that there is not a relationship (Sylvetsky-Meni et al, 2015). If parents do not perceive that their child is overweight/obese, it is possible that they will be less likely to engage in behavior change that facilitates a healthier weight for their child resulting in school-based childhood obesity interventions that incorporate families to fail (Eckstein et al, 2006;Min, Wang, Xue, Mi, & Wang, 2017;Rune, Mulgrew, Sharman, & Lovell, 2015;Wald et al, 2007).…”
mentioning
confidence: 99%
“…The statistical analysis was undertaken with SPSS version 17.0 software for Windows (IBM Corporation, Armonk, NY). The measurements were transformed into Z scores according to the Z score model for the levator hiatal area on the Valsalva maneuver, which was built on the basis of the nulliparous population by using the method documented in a previous study . The procedures for building the Z score model are described below.…”
Section: Methodsmentioning
confidence: 99%
“…The Z score, which is widely used in biometry, has been described as the measured value that deviates from the average level as a multiple of the standard deviations. It can be used to precisely quantify the difference between the individual value and the general level . In statistics, the Z score (ie, standard score) is the signed number of standard deviations by which the value of an observation or data point is above or below the mean value of what is being observed or measured.…”
mentioning
confidence: 99%